Factors Influencing the Sexual Function of Women with Urinary Incontinence - Miok Kim (Korean Society of Women Health Nursing, 2013)
PURPOSE: Sexual function involves a complex interaction of emotions, body image, and intact physical responses. The purpose of this study was to determine the sexual functioning of women who are incontinent and to identify associated factors. METHODS: For this descriptive correlation study, data were collected from 147 women with urinary incontinence. Data were analyzed using t-test, ANOVA, and stepwise multiple regression. RESULTS: Mean scores were 22.39 (sexual dysfunction < or =26.55) for sexual function, 13.38 (of 63) for depression, and 55.47 (range of score 17~85) for body image. Urinary symptoms and daily life symptoms averaged 36.04 (range of score 20~100) and 16.03 (range of score 8~40). Sexual function had a positive correlation with body image and negative correlation with daily life symptoms. Sexual satisfaction, daily life symptoms, marital satisfaction, and frequency of sexual intercourse were factors affecting sexual function. CONCLUSION: Study results indicate that urinary incontinence has a negative impact on various aspects of sexual function. Nurses should be aware of the wider consideration that needs to be made in relation to general and sexual quality of life when caring for clients suffering from urological diseases.